Gas-phase synthesis of oxymethylene ethers over Si-rich zeolites. Issue 20 (4th October 2018) - Grünert, Anna; Losch, Pit; Ochoa-Hernández, Cristina; Schmidt, Wolfgang; Schüth, Ferdi
Abstract : A new approach for production of potential diesel substitutes oxymethylene ethers via continuous gas-phase synthesis from methanol and formaldehyde over zeolite catalysts. Abstract : Oxymethylene ethers are a class of synthetic fuels that allows significantly reduced levels of pollutant emissions from compression-ignition engines. Conventionally they are synthesized in liquid-phase. As a new approach for the production of oxymethylene ethers the continuous gas-phase synthesis from methanol and formaldehyde was studied. A broad range of zeolites has been studied as the catalysts for the reaction and a relationship between reactivity and silica-to-alumina ratio was established. Moderate acidity as found in silicon-rich zeolites proved to be advantageous. Even aluminum-free zeolite shows high selectivity and activity to OME indicating that silanol groups as found on the external surface or in defects provide sufficient acidity for the reaction. The zeolitic catalysts deactivate with time but can be fully regenerated with common regeneration protocols.